Feeding and reflux in children after mandibular distraction osteogenesis for micrognathia: A systematic review. (June 2016) - Breik, Omar; Umapathysivam, Kandiah; Tivey, David; Anderson, Peter
Abstract: Mandibular distraction osteogenesis (MDO) is becoming increasingly more commonly used as in neonates and infants with upper airway obstruction secondary to micrognathia. A significant number of these children are dependent on nasoenteric feeding or gastrostomies after birth for adequate nutrition and often suffer from gastro-esophageal reflux (GERD). Objective: This analysis is a subset of a larger systematic review. The objective of this study is to determine the effects of MDO on feeding and GERD. Data sources: The databases searched included PubMed, Embase, Scopus, Web of Knowledge and grey literature sources. Study selection: The inclusion criterion included studies in children with clinical evidence of micrognathia/Pierre Robin Sequence (PRS) who have failed conservative treatments, including both syndromic (sMicro) and non-syndromic (iPRS) patients. 21 studies relevant to feeding and 4 studies relevant to GERD outcomes were included. All studies included were case series and case reports. Results: MDO leads to a significant improvement in feeding, with 82% of children feeding exclusively orally after surgery. The overall percentage of children with iPRS who were feeding orally was 93.7% compared with only 72.9% in the sMicro group ( p < 0.004). A growth decline within the first six weeks after surgery was observed in multiple studies. Overall, out of 70 patients with pre-operative GERD, only four had evidence of GERD after surgery. Conclusions: Considering the limitations of this systematic review, this study found that successful relief of airway obstruction by MDO leads to improvement of feeding and improvement in symptoms of GERD in children with upper airway obstruction secondary to micrognathia. Clinicians need to be aware of the risk of growth decline in the initial post-operative period.